Iatrogenic injury of the subclavian artery treated percutaneously with arterial closure device - Antunes,Inês (2020)
Introduction: Subclavian arterial puncture is a relatively frequent complication of attempted placement of central venous catheters (CVC). The placement of a CVC in the artery is rarer, but with potential serious complications especially in its withdrawal. Anticipating these complications, control of potential bleeding in catheter withdrawal is usually performed by surgical or endovascular approach with endoprosthesis release. Our goal is to present the treatment with a percutaneous arterial closure device. Materials / Methods: Presentation of a clinical case of a CVC placed in the subclavian artery treated with a percutaneous arterial closure device. Results: A 51-year-old man hospitalized for acute myocardial infarction. On the first day of hospitalization, the introduction of a CVC into the right subclavian vein was attempted. In view of the suspected intraarterial position, CT angiography scan demonstrated that the CVC had been introduced into the subclavian artery with a point of entry proximal to the passage under the clavicle and with a path to the brachiocephalic trunk. Hypocoagulation with UFH was initiated given the risk of pericateter thrombosis and embolization. The use of percutaneous closure device ProGlide® was planned using the CVC pathway. As predictable difficulties for this option was the long CVC path to the arterial entry point, raising questions about the extent of the suture mechanism of the device and the progression of nodes in this path. Under fluoroscopic control, an angioplasty balloon was progressed until the CVC point of entrance for temporary bleeding control in case of ProGlide® failure; in which case the procedure would be completed with a covered endoprosthesis; the subclavian artery had a diameter of 12 mm and was ipsilateral to a brachiocephalic fistula. It was decided to retrograde puncture the fistula and progress the balloon to the subclavian artery. The rigid guide wire was then placed through the CVC and the CVC removed. Two Proglide® closure devices (positioned at 10 p.m. and 2 p.m.) were released. The complete resolution of clinical and imaging hemorrhage was verified. Discussion/Conclusions: Placement of CVC in the subclavian artery is a potentially serious complication since its removal can be complicated with severe haemorrhage. Depending on the point of entry, there may be additional complexities due to the proximity of the vertebral and carotid arteries. In this case we left open several hypotheses (endovascular and ultimately surgical), but our preference was ad initium the percutaneous introduction of closure device given the feasibility, simplicity, less aggressiveness, non-interference with the vertebral ostium, and lower cost compared to a covered endoprosthesis.